Ostrea (Turkostrea) Doidoiensis Hasibuan from The Bayah Formation West Jawa: A New Find - Fauzie Hasibuan (Pusat Survei Geologi, 2006)
A species of Ostreidae conspecific with Ostrea (Turkostrea) doidoiensis Hasibuan from the Middle Eocene Malawa Formation, South SuIawesi, was also discovered from Bayah Formation, Banten, West Jawa. A juvenile form of the taxon is thought to occur in the Nanggulan Formation, Central Jawa, Correlation of the Â age of the formations is considered. Paleoenvironmental implication of the taxon and its distribution inÂ Indonesia are discussed.Keywords: Ostrea (Turkostrea) doidoensis, Bayah formation, Malawa formation, Middle Eocene, RV (right valve). LV (left valve)